The right choice : a public health campaign for primary schools - Chek, Yin Kuan (2015)
This paper presents “The Right Choice”, a public health campaign by four final year undergraduates at the Wee Kim Wee School of Communication and Information (WKWSCI) in Nanyang Technological University (NTU). This campaign aimed to combat the rising trend of childhood obesity in Singapore which has increased multiple-fold in the last few decades. Obesity is a key cause of multiple serious diseases such as diabetes, emphasising the need to focus on the issue of obesity to alleviate these serious health problems. Primary school children aged 7 to 12 years old were the campaign’s primary target audience, as eating habits developed at a young age tend to stay for a very long time. Their parents were the secondary target audience as they are the main gatekeepers to the children’s diets. Using a game-based learning approach to engage children, a computer game and game booths were developed to empower children to adopt good dietary habits. Through positive messaging and reinforcement, the campaign hoped to educate children and parents to adopt and sustain healthy eating habits. Findings indicated that game-based learning proved to be popular among the children as most reported high levels of fun experienced. Positive attitudes were displayed towards game-based learning and the perception of the different activities. The approach proved effective in engaging children on a serious topic such as health and nutrition, with further indication that it could work for other types of issues as well.